2017
DOI: 10.1111/cge.13010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, clinical and neuropsychological study in 31 patients with Kabuki syndrome and KMT2D mutations

Abstract: Kabuki syndrome (KS-OMIM 147920) is a rare developmental disease characterized by the association of multiple congenital anomalies and intellectual disability. This study aimed to investigate intellectual performance in children with KS and link the performance to several clinical features and molecular data. We recruited 31 children with KMT2D mutations who were 6 to 16 years old. They all completed the Weschler Intelligence Scale for Children, fourth edition. We calculated all indexes: the Full Scale Intelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 18 publications
3
46
1
1
Order By: Relevance
“…The degree of intellectual disability typically falls in the mild to moderate range, with severe intellectual disability being uncommon. However, not every person with KS will have intellectual disability,7 27–33 and this feature cannot be assessed in a newborn or infant 27. Caciolo et al 28 performed standardised neuropsychiatric testing on a cohort of 17 individuals with KS (9 of whom had a confirmed heterozygous pathogenic variant in KMT2D and 8 of whom had a clinical diagnosis of KS) and found that there were no significant differences in the neuropsychological profile between those with a molecular diagnosis and those with a clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of intellectual disability typically falls in the mild to moderate range, with severe intellectual disability being uncommon. However, not every person with KS will have intellectual disability,7 27–33 and this feature cannot be assessed in a newborn or infant 27. Caciolo et al 28 performed standardised neuropsychiatric testing on a cohort of 17 individuals with KS (9 of whom had a confirmed heterozygous pathogenic variant in KMT2D and 8 of whom had a clinical diagnosis of KS) and found that there were no significant differences in the neuropsychological profile between those with a molecular diagnosis and those with a clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although its phenotypic spectrum is relatively well characterized in Caucasian and Japanese populations, only limited and incomplete information is available in Chinese populations (Guo et al, ). In the present study we report the detailed phenotypes of 14 patients with KS from two tertiary Children's Hospitals in China in addition to the phenotype from 11 Chinese patients with KS that were identified through a comprehensive literature search (Lehman et al, ). The relatively low number of reported patients with KS in China may have several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they found that many patients had much higher verbal comprehension and working memory scores than perceptual reasoning and processing speed scores (Lehman et al . ). More recently, a study by Caciolo et al .…”
Section: Introductionmentioning
confidence: 97%
“…Lehman et al . () studied 31 patients with documented KMT2D disease‐causing variants. They found that those with nonsense variants had lower full scale IQs than those with other disease‐causing variants.…”
Section: Introductionmentioning
confidence: 99%